2017
DOI: 10.5543/tkda.2017.86344
|View full text |Cite
|
Sign up to set email alerts
|

The Choice of Treatment Based on Turkish Hypertension Consensus Report: Do We Follow The Recommendations?

Abstract: Antihypertensive therapies were individualized, as suggested by the consensus report. However, there are proposals still to be considered in special patient groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 0 publications
1
4
0
4
Order By: Relevance
“…In addition, unlike the guidelines according to the ATC-2 subclassification, diuretics were the fourth chosen drug whereas according to the ATC-5 subclassification a high-ceiling diuretic, furosemide was the third-chosen drug in hypertension treatment. In a study conducted in Turkey and in Nigeria, diuretics was the most preferred drugs [15,16]. In this study, it was observed that the most common prescribed diuretics were the highceiling diuretics and potassium-sparing agents.…”
Section: Pharmacotherapy Of Hypertension In North Cyprus фармакотерапmentioning
confidence: 75%
See 4 more Smart Citations
“…In addition, unlike the guidelines according to the ATC-2 subclassification, diuretics were the fourth chosen drug whereas according to the ATC-5 subclassification a high-ceiling diuretic, furosemide was the third-chosen drug in hypertension treatment. In a study conducted in Turkey and in Nigeria, diuretics was the most preferred drugs [15,16]. In this study, it was observed that the most common prescribed diuretics were the highceiling diuretics and potassium-sparing agents.…”
Section: Pharmacotherapy Of Hypertension In North Cyprus фармакотерапmentioning
confidence: 75%
“…В дополнение к этому, в отличие от рекомендаций по подклассу АТХ-2, диуретики являлись четвертыми по частоте назначения; по подклассу АТХ-5 петлевой диуретик фуросемид был третьим по назначаемости препаратом при АГ. По данным исследований, проведенных в Турции и Нигерии, диуретики являлись наиболее предпочтительными средствами [15,16]. Настоящее исследование выявило, что назначенные диуретики в основном относились к группам петлевых и калийсберегающих, и такие результаты позволили предположить, что врачи избегают применять диуретики в качестве препаратов выбора из-за их побочного действия в виде гипокалиемии.…”
Section: Discussionunclassified
See 3 more Smart Citations